Differential specificity for binding of retinoblastoma binding protein 2 to RB, p107, and TATA-binding protein. - Kim, Y W (1994)
The growth suppressor activities of the RB and p107 products are believed to be mediated by the reversible binding of a heterogeneous family of cellular proteins to a conserved T/E1A pocket domain that is present within both proteins. To study the functional role of these interactions, we examined the properties of cellular retinoblastoma binding protein 2 (RBP2) binding to RB, p107, and the related TATA-binding protein (TBP) product. We observed that although RBP2 bound exclusively to the T/E1A pocket of p107, it could interact with RB through independent T/E1A and non-T/E1A domains and with TBP only through the non-T/E1A domain. Consistent with this observation, we found that a mutation within the Leu-X-Cys-X-Glu motif of RBP2 resulted in loss of ability to precipitate p107, while RB- and TBP-binding activities were retained. We located the non-T/E1A binding site of RBP2 on a 15-kDa fragment that is independent from the Leu-X-Cys-X-Glu motif and encodes binding activity for RB and TBP but does not interact with p107. Despite the presence of a non-T/E1A binding site, however, recombinant RBP2 retained the ability to preferentially precipitate active hypophosphorylated RB from whole-cell lysates. In addition, we found that cotransfection of RBP2 can reverse in vivo RB-mediated suppression of E2F activity. These findings confirm the differential binding specificities of the related RB, p107, and TBP proteins and support the presence of multifunctional domains on the nuclear RBP2 product which may allow complex interactions with the cellular transcription machinery.